UMKM AND VILLAGE SYNERGY: A COMMUNITY SERVICE MODEL FOR SUSTAINABLE GROWTH - Albert Yansen; Mansur Saparang, Ependi (JOURNAL OF COMMUNITY DEDICATION, 2024)
The synergy model between Micro, Small and Medium Enterprises (MSMEs) and villages as a community service strategy to promote sustainable growth. This model emphasises the importance of collaboration between MSMEs that have innovative potential and high adaptive power with abundant resources in villages, to create new economic opportunities and improve the welfare of local communities. The findings from this study found that the synergy between MSMEs and villages brings not only economic benefits, but also significant social impacts, by improving the skills, knowledge and social cohesion of village communities. While the benefits are many, the implementation of this model faces challenges such as infrastructure limitations and skills gaps. Therefore, support from various parties, including the government, financial institutions, and educational institutions, is needed to create an ecosystem that supports and encourages the success of this synergy. This research confirms that the synergy of MSMEs and villages is a strategic approach that is not only innovative but also important in realising inclusive and sustainable economic growth.